Plants Defense-related Cyclic Peptides: Diversity, Structure and Applications. - Maria, Ana Carolina Wanderley-Nogueira; Bezerra-Neto, João Pacífico; Kido, Éderson Akio; de Araújo, Flávia Tadeu; Amorim, Lidiane Lindinalva Barbosa; Crovella, Sergio; Benko-Iseppon, Ana Maria (Curr Protein Pept Sci, 2016)
Plant growth is prone to several unfavorable factors that may compromise or impair development and survival, including abiotic or biotic stressors. Aiming at defending themselves, plants have developed several strategies to survive and adapt to such adversities. Cyclotides are a family of plant-derived proteins that exhibit a diverse range of biological activities including antimicrobial and insecticidal activities that actively participate in plant defense processes. Three main categories of peptides have been described: (i) Cyclotides (ii) Sunflower Trypsin Inhibitor (SFTI) and (iii) peptides MCoTI-I and II, from Momordica cochinchinensis. They comprise proteins of approximately 30 amino acids, containing a head-to-tail cyclized backbone, with three disulfide bonds configured in a cystine knot topology, therefore bearing greater peptide stability. Given their features and multifunctionality, cyclotides stand out as promising sources for the discovery of new antimicrobial agents. The present review describes cyclotide occurrence, abundance and action in plants, also their diversity and evolution. Considerations regarding their use in the context of biomedical and agronomical sciences uses are also presented.